(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The experiment was conducted at Ifite Ogwari, Anambra State to evaluate the effects of some soil amendments on thegrowth and yield performance of Okra (Abelmoschus esculentus). The experiment was laid out in a completely randomized design (CRD) with three (3) replications and an Okra variety made up my treatment. This experiment was carried out in a pottedbag with a total of (24) treatments including the control experimental bag. Data on growth and yield parameters were collected and analyzed using analysis of variance (ANOVA) for completely randomized design. The treatment means were separated using least significant difference at 5% probability level. The results obtained showed that treatment T8 (poultry manure + rice husk + compost + cow dung) performed significantly well in plant height and number of leaves, while on the other hand treatment T5 ( poultry manure + rice husk + top soil ),T2 ( poultry manure + top soil ) and T3( cow dung + top soil) performed notably better with respects to leaf area , number of fruits, stern girth and fruit weight.